2020
DOI: 10.1007/s00221-020-05917-5
|View full text |Cite
|
Sign up to set email alerts
|

The direction of postural threat alters balance control when standing at virtual elevation

Abstract: Anxiogenic settings lead to reduced postural sway while standing, but anxiety-related balance may be influenced by the location of postural threat in the environment. We predicted that the direction of threat would elicit a parallel controlled manifold relative to the standing surface, and an orthogonal uncontrolled manifold during standing. Altogether, 14 healthy participants (8 women, mean age = 27.5 years, SD = 8.2) wore a virtual reality (VR) headset and stood on a matched real-world walkway (2 m × 40 cm ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…Thus, the increased body sway velocity in high fear participants suggests that they may not be able to use sensory feedback adequately when exposed to heights. We also observed that the magnitude of body sway decreased with ascending virtual height (similarly in both groups), which is in line with some of the previous reports ( Cleworth et al, 2012 ; Raffegeau et al, 2020 ), but not others ( Simeonov et al, 2005 ; Wuehr et al, 2019 ; Chander et al, 2021 ). The reasons for such inconsistent findings across the studies are not clear.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Thus, the increased body sway velocity in high fear participants suggests that they may not be able to use sensory feedback adequately when exposed to heights. We also observed that the magnitude of body sway decreased with ascending virtual height (similarly in both groups), which is in line with some of the previous reports ( Cleworth et al, 2012 ; Raffegeau et al, 2020 ), but not others ( Simeonov et al, 2005 ; Wuehr et al, 2019 ; Chander et al, 2021 ). The reasons for such inconsistent findings across the studies are not clear.…”
Section: Discussionsupporting
confidence: 93%
“…Second, also inconsistent are the reports on the effect of virtual height exposure on postural balance. While Cleworth et al (2012) found that body sway magnitude decreased during exposure to height in VR, several other studies reported the opposite effect, i.e., an increase in the magnitude of body sway (Wuehr et al, 2019;Raffegeau et al, 2020;Chander et al, 2021). Furthermore, it has been reported that postural reactions to simulated height are independent of individual height intolerance and the elicited fear (Wuehr et al, 2019), in contrast to real height exposure when postural adjustments were related to individual fear and anxiety levels (Davis et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, visual manipulations in experimental and clinical settings use virtual reality (VR) to alter immersive virtual environments (VE) for rehabilitation [24]. VR has also been used to expose individuals to VE that can induce postural threats, such as simulated vertical heights [8,9,[25][26][27] and rotating the visual field on the pitch, yaw, and roll principle axes [26,28], that alter center of pressure (COP) dynamics and bodily kinematics and thereby, the overall postural stability. Moreover, VR is identified as a great alternative to expose individuals to different environments they otherwise avoid due to fear [8,29].…”
Section: Introductionmentioning
confidence: 99%